Bulbophyllum xiajinchangense (Orchidaceae; Malaxideae), a new species from China: evidence from morphological and DNA analysis - Zeng, Meng-Yao; Wu, Yu-Wei; Wei, Chun-Yi; Wu, Yu-Han; Li, Ming-He (Phytotaxa, 2023)
Bulbophyllum xiajinchangense (Orchidaceae), a new species from Yunnan province, China, is described and illustrated. It is morphologically similar to B. scabratum, but differs by its free (vs. convergent) lateral sepals, the ratio of mean lateral/dorsal sepal length (ca. 2.0 vs. ca. 3.0), purplish-red (vs. pale yellow-ochre) flowers. Phylogenetic analysis based on nuclear ribosomal ITS and two plastid (matK and psbA-trnH) sequences support B. xiajinchangense as a distinct species, which forms an independent lineage sister to B. levinei, B. gedangense and its allies.